A Comprehensive Review of Artificial Intelligence in Prevention and Treatment of COVID-19 Pandemic - Wang, Haishuai; Jia, Shangru; Li, Zhao; Duan, Yucong; Tao, Guangyu; Zhao, Ziping (Frontiers in Genetics, 2022)
The unprecedented outbreak of the COVID-19 pandemic has seriously affected numerous countries in the world in terms of various aspects such as education, economy, social security, public health and many other aspects. Most governments have made great efforts to control the spread of COVID-19, e.g., locking down hard-hit cities and advocating masks for population. Due to the relatively poor medical conditions in some countries and regions with insufficient medical equipment, hospital capacity overload, personnel shortage and other problems, resulting in the large-scale spread of the epidemic. With the unique advantages of artificial intelligence (AI), it plays an extremely important role in medical imaging, clinical data, drug development, epidemic prediction, and telemedicine. Therefore, AI is a powerful tool that can help humans solve complex problems, especially in the fight against COVID-19. This study aims to analyze past research results and interpret the role of Artificial Intelligence in the prevention and treatment of COVID-19 from five aspects. In this paper, we also discuss the future development direction of different fields and prove the validity of the models through experiments, which will help researchers develop more efficient models to control the spread of COVID-19.